2016
DOI: 10.1017/jfm.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

DNS study of particle-bed–turbulence interactions in an oscillatory wall-bounded flow

Abstract: Particle-resolved direct numerical simulations (DNS) are performed to investigate the behaviour of an oscillatory flow field over a rough bed, corresponding to the experimental set-up of Keiller & Sleath (J. Fluid Mech., vol. 73 (04), 1976, pp. 673-691) for transitional and turbulent flows over a range of Reynolds numbers (95-400) based on the Stokes-layer thickness. It is shown that the roughness modulates the near-bed turbulence, produces streamwise horseshoe structures which then undergo distortion and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
4
22
0
1
Order By: Relevance
“…Similar numerical simulations were made by substituting the semispheres with spherical particles thus obtaining a geometry more similar to that used in previous experiments (Keiller & Sleath, 1976). Two different numerical studies (Ghodke & Apte, 2016; both considering a similar geometry, independently confirm the presence of vortices released by the roughness elements at flow reversal, a phenomenon which is also observed in laboratory experiments of oscillatory flow over regular roughness elements (Krstic & Fernando, 2001).…”
Section: Introductionsupporting
confidence: 64%
“…Similar numerical simulations were made by substituting the semispheres with spherical particles thus obtaining a geometry more similar to that used in previous experiments (Keiller & Sleath, 1976). Two different numerical studies (Ghodke & Apte, 2016; both considering a similar geometry, independently confirm the presence of vortices released by the roughness elements at flow reversal, a phenomenon which is also observed in laboratory experiments of oscillatory flow over regular roughness elements (Krstic & Fernando, 2001).…”
Section: Introductionsupporting
confidence: 64%
“…The TKE budget based on the PIV data obtained in present measurement is analyzed. The production terms included in the TKE budget equation are hereby mainly concerned, including the productions from the streamwise stress P uu and shear stress P uv , which are denoted as [42,43]…”
Section: Production Of Turbulent Kinetic Energymentioning
confidence: 99%
“…The approach could be applied to shallow water waves to assess the effect of wind on increasing the bottom shear stress and linking it to disruption of the log layer. Turbulence greatly affects material transport; recently, Ghodke et al [49,50] in their groundbreaking and fully resolved numerical study reported the effects of turbulence on incipient material transport mechanisms. Such high-fidelity simulations can further provide time-accurate eddy viscosity data that otherwise are extremely challenging to obtain using experiments.…”
Section: Discussionmentioning
confidence: 99%